The Effect of Financial Literacy on Investment Decisions with Financial Wellbeing as a Mediating Variable (A Study on Cryptocurrency Investors in Bali Province) - Akmalluddin Alghani; I Gusti Bagus Wiksuana (PT. Publikasiku Academic Solution, 2026)
Cryptocurrencies have emerged as a volatile yet increasingly popular investment vehicle worldwide, attracting millions of retail investors despite significant price fluctuations and limited regulatory frameworks. Understanding the factors that drive investment decisions in this high-risk context is critical for both investor protection and market stability. The purpose of this study is to examine the effect of financial literacy on investment decisions mediated by financial well-being in Bali Province. The population in this study consists of all investors who have invested in cryptocurrency in Bali Province. The sampling method used in this study is nonprobability sampling, with a total sample size of 345 respondents. The analysis technique used in this study is PLS-based SEM. The results show that financial literacy has a positive and significant effect on investment decisions. Financial well-being acts as a partial mediator in the relationship between financial literacy and investment decisions among cryptocurrency investors in Bali Province. The theoretical implications of this study provide empirical contributions regarding the relationships among financial literacy, financial well-being, and investment decisions, advancing financial behavior theory. The practical implications are that cryptocurrency investors can improve their financial literacy and financial well-being to enhance their investment decisions, and cryptocurrency exchanges can provide insights about cryptocurrencies to investors to support better decision-making.